2017
DOI: 10.1016/j.atherosclerosis.2017.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of K-877, a novel selective peroxisome proliferator-activated receptor α modulator (SPPARMα), in combination with statin treatment: Two randomised, double-blind, placebo-controlled clinical trials in patients with dyslipidaemia

Abstract: These results strongly support the favourable benefit-to-risk ratio of K-877 add-on therapy in combination with statin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
62
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 46 publications
16
62
0
1
Order By: Relevance
“…The gamma‐glutamyl transpeptidase level significantly decreased and the ALT level decreased, although this change was not statistically significant, in the present study. Previous studies on the effects of pemafibrate reported significant decreases in both gamma‐glutamyl transpeptidase and ALT levels. Patients with non‐alcoholic fatty liver disease (NAFLD) have higher HOMA‐IR and/or lower GIR levels than those without NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The gamma‐glutamyl transpeptidase level significantly decreased and the ALT level decreased, although this change was not statistically significant, in the present study. Previous studies on the effects of pemafibrate reported significant decreases in both gamma‐glutamyl transpeptidase and ALT levels. Patients with non‐alcoholic fatty liver disease (NAFLD) have higher HOMA‐IR and/or lower GIR levels than those without NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…22 Phase 2 and 3 studies demonstrated that pemafibrate treatment, with or without statins, resulted in a significant decrease in fasting TG level and increase in HDL-C level and suggested that pemafibrate may have a superior risk/benefit profile to fenofibrate. [23][24][25][26][27] In vivo and in vitro studies found that pemafibrate enhanced CEC, RCT, and TRL catabolism, suppressed TRL production, and exerted anti-inflammatory and antiatherosclerotic effects. 28 Therefore, the present study aimed to investigate the effects of pemafibrate on CEC and postprandial hyperlipidemia in patients with atherogenic dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies are needed to demonstrate whether clinical interventions targeting [HDL‐C/apoA‐I] or other aspects of dyslipidaemia (which would otherwise improve this ratio and the derived indices) will decrease microvascular and/or macrovascular outcomes . Relevant interventions should a priori improve the ratio by a magnitude such as the one separating 2 quartiles, or ideally move this ratio by a value approaching the difference among 2 or even 3 ascending quartiles.…”
Section: Discussionmentioning
confidence: 99%